Role of TCP Gene BRANCHED1 in the Control of Shoot Branching in Arabidopsis - Poza-Carrión, César (Landes Bioscience, 2007)
Branching patterns are major determinants of plant architecture. They depend both on leaf phillotaxy (branch primordia are formed in the axils of leaves) and on the decision of buds to grow out to give a branch or to remain dormant. In Arabidopsis, several genes involved in the long-distance signalling of the control of branch outgrowth have been identified. However, the genes acting inside the buds to cause growth arrest remained unknown until now. In the February issue of Plant Cell we have described the function of BRANCHED1 (BRC1), an Arabidopsis gene coding for a plant-specific transcription factor of the TCP family that is expressed in the buds and prevents their development. Loss of BRC1 function leads to accelerated AM initiation, precocious progression of bud development and excess of shoot branching. BRC1 transcription is affected by endogenous and environmental signals controlling branching and we have shown that BRC1 function mediates the response to these stimuli. Therefore we have proposed that BRC1 function represents the point at which signals controlling branching are integrated within axillary buds.